Assessment of factors influencing fuelwood utilization in Makurdi metropolis, Benue state, Nigeria - Ancha, Paul Utser; Sambe, Leoskali Nguuma; Peter, Lilian Chinenye (Journal of Forests, 2024)
The study was conducted to assess the factors influencing the utilization of fuelwood in Makurdi metropolis due to the paucity of information on the factors in the area. Simple random sampling technique was used to select 125 people in 25 houses from five locations in the study area. Data for the study was obtained through a semi-structured questionnaire, interview, and personal observation. Field data was analyzed using descriptive, Likert scale rating and regression models. Results of analysis of field data show that seven tree species were utilized for fuelwood in the study area with Prosopis africana (34%) being the most preferred fuelwood spp utilized while Burkia africana (2.1%) was the least utilized fuelwood spp. The Multilinear regression model was selected as the best-fit model in explaining the factors influencing fuelwood utilization in the study area based on its high r2 value and low standard error estimated compared to the other three regression models. None of the socioeconomic variables investigated had a significant influence on fuelwood utilization (P > 0.05). However, age, income, family size, unit price, and availability of the commodity positively influence fuelwood utilization in the study area. The socioeconomic factors were able to explain 67% of the variation in fuelwood utilization in Makurdi Metropolis. Fuelwood is highly utilized in the area. Therefore, the conservation of the preferred fuelwood tree species in community forests and agroforestry practices should be encouraged by the Government, Non-governmental organizations (NGOs), and private individuals to enhance the sustainability of the resource.